Law making and the Scottish Parliament : the early years - Sutherland, Elaine (Edinburgh studies in law, 2011)
Law Making and The Scottish Parliament: The Early Years offers the first wide-ranging critical analysis of legislative developments in those areas of law and policy devolved to the Scottish Parliament under the devolution settlement. It begins with a brief account of the devolution settlement and summarises the themes emerging from the subsequent chapters. Thereafter, sixteen themed chapters, each dedicated to a discrete area of the law and written by an acknowledged expert in the field, provide critical evaluation of the Scottish Parliament's contribution, highlighting what it has achieved, what it has failed to do and what might be done in the future. In a single volume, Law Making and The Scottish Parliament: The Early Years provides a scholarly evaluation of a number of legislative achievements of Scotland's devolved parliament in its first decade. It will appeal to legal and other scholars and students, lawyers and anyone with an interest in Scottish politics, policy-making and law .